The Function of State Administrative Courts in Supporting Good Government Free From Corruption - Mabsuti, Mabsuti; Fithroh, Muidatul; Anfal, Sofiatul; Mulyani, Intan Tri; Fasya, M. Farhan Aishwar; Ibrahim, Ilman (Fox Justi : Jurnal Ilmu Hukum, 2025)
The State Administrative Court (PTUN) holds a strategic role in promoting a transparent, accountable, and corruption-free government. As a judicial mechanism to review the legality of state administrative decisions (KTUN), PTUN serves as an essential instrument for ensuring transparency, accountability, and legal certainty—core pillars of good governance. Additionally, PTUN contributes to anti-corruption efforts by addressing abuses of power within bureaucratic decision-making. Despite its importance, PTUN's effectiveness is hampered by several challenges, including low public legal awareness, limited jurisdictional reach, and insufficient integration with national anti-corruption enforcement bodies. Strengthening PTUN's institutional capacity, reforming the administrative justice system, and enhancing inter-agency collaboration are necessary steps to empower PTUN as a more effective actor in the fight against corruption. This article explores the role of PTUN in supporting good governance, identifies key obstacles to its optimal performance, and offers strategic recommendations to strengthen its contribution to a clean, law-abiding government. Ultimately, PTUN should be positioned as a vital component of Indonesia's long-term governance reform agenda.